PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS LMS MOODLE DITINJAU DARI COGNITIVE LOADS THEORY - nuryadi nuryadi (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2020)
The development of E-Learning is based on the development of IPTEK as a resource for the fulfillment of core competencies in curriculum 2013 which facilitate students and teachers in the learning process.The research uses R&D design, based from cognitive loads theory with the Borg & Gall development model. The steps are: research and information collection, research planning, initial product development, preliminary field test involving 4 students, revision of preliminary field test result, wider field test involving 8 students, test revision A field, a feasibility test involving 32 students, and a revision of the feasibility of a trial subject in research is a grade VIII student of SMP Negeri 1 Mlati, Kab. Sleman, D.I. Yogyakarta. Data is collected through polls and observations during trials, and then research results are analyzed with quantitative descriptive analysis techniques. Media expert responses get an average score of 3.91. While the responses of the material experts acquired an average score of 3.60 showed a Moodle-based e-learning is decent in terms of media and worthy of material terms. The results of the study on field implementation test show that all students of class VIII C percentage of class submission are above 86%. The results of the students ' responses to small and large scale trials showed that the majority of students gave positive feedback on learning activities using LMS Moodle-based e-learning media. LMS Moodle's final e-learning product contains material, video links, ppt links, quizzes, articles around mathematical numeral patterns, chat and discussion forums. Thus, from the test results of the implementation of the field can be concluded that E-learning based on LMS Moodle Mathematics learning for students of grade VIII C SMP Negeri 1 Mlati, with material